REVIEW PENELITIAN TENTANG PERILAKU INVESTOR DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Hartini, Umi; Utomo, Dwi Cahyo (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
The purpose of this research is to systematically review the literature published ini past 42 years on behavioural biases in investment decision making. This paper highlights the major gaps in the existing studies on behavioural biases. It also aims raise specific questions for future research. The design of this research employ systematic literature review (SLR) method in the present study. The prominence research is assessed by studying the year of publication, journal of publication, country of study, types of statistical method, data collection technique and content analysis on literature on behavioural biases. The present study is based on 41 selected articles published in peer review journals between 1980 and 2022. The result show that much of the existing literature on behavioural biases indicates the limited research in developed economies in this area, the dominance of the primary data on data collection technique, the lack of empirical research on individuals who exhibit herd behaviour, the dominance theory used in the existing literature on behavioural biases in investment decision making is prospect theory.